Mapping Ground Water Quality in Sri Muktsar Sahib District, Punjab Using Geo-statistics - Kundu, Debjani; Sood, Anil (International Journal of Economic Plants, 2025)
Systematic survey was carried out to assess the ground water quality of Muktsar district of Punjab using geo-statistics during post monsoon season (December–February) 2013–14. Geo-referenced ground water samples were collected in regular grid in post monsoon season; and analysed for pH, electrical conductivity (EC), total hardness (Ca2++Mg2+), sodium (Na+) and potassium (K+), carbonate and bi-carbonate (CO32-, HCO3-), chloride (Cl-) and sulphate (SO4–2). Residual Sodium Carbonate (RSC) and Sodium Adsorption Ratio (SAR) were calculated using standard formula. Ground water quality was evaluated on the basis of EC and RSC. Spatial distribution of ground water quality parameters and overall, ground water quality was assessed and mapped though geostatistical approach. The best semi-variogram model for every parameter varied based on the root mean square error (RMSE) criterion. Salinity hazard in ground water was prominent in the eastern and southern part of the district and 41.1% of total geographic area (TGA) of the district was irrigated with highly to extremely saline ground water (EC>4 and >6 dS m-1, respectively and RSC<2.5 me l-1). Non saline non sodic ground water (EC<2 dS m-1 and RSC<2.5 me l-1) was available only in 10.6% of TGA whereas, slight to moderate sodic ground water prevailed in a very small area (1.6% of TGA of the district). Mixing of canal water with ground water, selection of appropriate crops, salt tolerant varieties may be alternative measures for rational use of water and preventing further deterioration.